2011
DOI: 10.1111/j.1471-4159.2011.07222.x
|View full text |Cite
|
Sign up to set email alerts
|

Calpastatin, an endogenous calpain-inhibitor protein, regulates the cleavage of the Cdk5 activator p35 to p25

Abstract: J. Neurochem. (2011) 117, 504–515. Abstract Cyclin‐dependent kinase 5 (Cdk5) is a Ser/Thr kinase that is activated by binding to its regulatory subunit, p35. The calpain‐mediated cleavage of p35 to p25 and the resulting aberrant activity and neurotoxicity of Cdk5 have been implicated in neurological disorders, such as Alzheimer’s disease. To gain further insight into the molecular mechanisms underlying the pathological function of Cdk5, we investigated the role of the calpain inhibitor protein calpastatin (CAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 49 publications
2
18
0
Order By: Relevance
“…In agreement with this finding, calpains -particularly m-and m-calpain -are abnormally activated in AD (Saito et al, 1993). Similarly, calpastatin, an endogenous inhibitor of calpains, is substantially decreased in AD (Nixon, 2003), which could lead to deregulation of Cdk5 through increased formation of p25 (Sato et al, 2011). Although a few in vitro studies have shown that the complex between Cdk5 and p25 displays a higher activity than that between Cdk5 and p35, other studies have reported comparable activities (Peterson et al, 2010).…”
Section: Introductionsupporting
confidence: 57%
“…In agreement with this finding, calpains -particularly m-and m-calpain -are abnormally activated in AD (Saito et al, 1993). Similarly, calpastatin, an endogenous inhibitor of calpains, is substantially decreased in AD (Nixon, 2003), which could lead to deregulation of Cdk5 through increased formation of p25 (Sato et al, 2011). Although a few in vitro studies have shown that the complex between Cdk5 and p25 displays a higher activity than that between Cdk5 and p35, other studies have reported comparable activities (Peterson et al, 2010).…”
Section: Introductionsupporting
confidence: 57%
“…The cleavage of TDP-43 was induced by incubation of the extracts in the presence of 5 mM CaCl 2 at 30 1C (ref. 58). The SDS sample buffer was added to stop the reaction.…”
Section: Constructionmentioning
confidence: 99%
“…−3, −9) are tissue-specific. 5 Activated calpain by calcium causes damage to cells by selectively degrading intracellular proteins, including signaling proteins (eg, cyclin-dependent kinase, protein kinase C) 6, 7 , cytoskeletal proteins (eg, talin, spectrin) 8, 9 , and transcription factors (eg, c-Jun, IkB). 1012 Calpains play a critical role in cellular apoptosis through the activation of both caspase-dependent and caspase-independent pathways.…”
Section: Introductionmentioning
confidence: 99%